Exploring the Unique Features of a First Nations Graduate-Level Social Work Program (Journal of Comparative Social Work, 2012)
Recently, a one-time cohort of graduate-level social work students completed a unique MSW program. The program was delivered in partnership between the Faculty of Social Work, University of Calgary and Blue Quills First Nations College and, of the twenty four graduates; twenty-one were of First Nations or Me´tis ancestry. The program honored traditional knowledge and ways of learning combined with a critical analysis of Western perspectives of social work knowledge. Strong fiscal resources enabled the program to establish a formal support network for the students and to support the development of Indigenous curriculum and programming that encouraged success for the students. The program was fundamentally different than urban on-campus programs while still maintaining graduate level accreditation requirements. This analysis of the program required the use of Indigenous Research Methodology to collect and create an understanding of the program. Instructors commented on the centered, empowered, balanced, and congruent students. The formal and informal, concrete and invisible supports to the students ensured the success of this program and this cohort of students. As one student commented, the program started in ceremony, ended in ceremony, and could not fail within the context ceremony.